مشروع حذف الاصفار من الدينار العراقي : تداعياته ومنافعه - الشكرجي، بشار ذنون محمد; الدليمي، شهاب حمد شيحان Aldulaimi, Shehab Hamad Shihan; الهاشمي، ليلى عبدالكريم محمد (جامعة الأنبار - كلية الإدارة والاقتصاد, 2012)
تناول البحث مشروع حذف الأصفار الثلاثة من الدينار العراقي تداعياته ومنافعه وكلفه المحتملة على دخل المواطن ومجمل الحركية الاقتصادية في داخل البلد أو على علاقاته التجارية مع مختلف دول العالم. وقد تناول البحث نظرياً مصطلح (Redenomination) لتميزه عن مصطلحات تخفيض العملة أو التبديل الجزئي للعملة كما هو الحال في الاتحاد الأوربي. وقد استقرأ البحث التجربة التركية في حذف (6) أصفار من الليرة (العملة الوطنية) باعتبارها من أحدث التجارب وأكثرها تميزا في استهداف التضخم. وخلص البحث العديد من الاستنتاجات، لعل أبرزها إن اختيار التوقيت المناسب لإجراء حذف الثلاثة أصفار بعد الاستقرار الاقتصادي في البلد سيسهم في استهداف التضخم وإعادة الثقة بالدينار العراقي كمخزن للقيمة ومن ثم تنشيط مجمل الاقتصاد العراقي. The research deals with die Redenomination of three zeros from Iracqi Dinar and the probability of its benefits and eo:t: up on the income of the citizen and its effect upon the economic movement: inside the country and upon the commercial relationship with the different countiies of the world. \ The research deal: with the teim "Redenomination” to differentiate it from other teims like reducing its financial value or partial exchanging asitis m the European union .The research depend: on the Turkish experiment in deleting six zero: from it: local currency (Turkish lira)This is con:idered the most modem experiment to treat the inflation .The research conclude: to many conclusion. \ The most important are chogsing the suitable time line of Redenomination after the stability of the economy m die county. This will lead to solve the problem of inflation and reconsider the confidence in Iraqi dinar a: a stock of value and to activate the Iraqi economy.
803526
Keywords: الاحوال السياسية -- النقود -- الدينار -- العراق -- السياسة النقدية -- الاستقرار الاقتصادي -- العملات